2015
DOI: 10.3390/ijms16035779
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Ti-Nb-Sn Alloy Implants with a Low Young’s Modulus

Abstract: Dental implants are widely used and are a predictable treatment in various edentulous cases. Occlusal overload may be causally related to implant bone loss and a loss of integration. Stress concentrations may be diminished using a mechanobiologically integrated implant with bone tissue. The purpose of this study was to investigate the biomechanical behavior, biocompatibility and bioactivity of a Ti-Nb-Sn alloy as a dental implant material. It was compared with cpTi. Cell proliferation and alkaline phosphatase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Moreover, recent works have reported the ability of niobium ions to enhance differentiation and mineralization of osteogenic cells in vitro 24 , 25 . Metallic niobium has been used in titanium alloys for endosseous implants, aiming to increase the biocompatibility and corrosion resistance, with superior fatigue resistance 27 . Similar behaviour of phosphate bioactive glass was observed on adding Nb 2 O 5 23 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent works have reported the ability of niobium ions to enhance differentiation and mineralization of osteogenic cells in vitro 24 , 25 . Metallic niobium has been used in titanium alloys for endosseous implants, aiming to increase the biocompatibility and corrosion resistance, with superior fatigue resistance 27 . Similar behaviour of phosphate bioactive glass was observed on adding Nb 2 O 5 23 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that Ti-Nb-Sn alloy implant with a low Young's modulus has biomechanical properties (hydrophilicity, ability to induce cell proliferation, and alkaline phosphatase activity) similar to those of Ti, and gives excellent osseointegration (values from pushin tests) 20) . In this study, we performed fluorescent morphological observations of ST-2 cells on a substrate and bone morphogenesis around implants.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that this Ti-Nb-based alloy containing Nb is easily fabricated by conventional cold working or plastic forming processes followed by heat treatment 21) . Surface characterization details were reported in our previous paper 20) . Briefly, these specimens were mechanically polished with a lathe machine regulated at 15 μm intervals.…”
Section: Specimen Designmentioning
confidence: 99%
See 2 more Smart Citations